Lung parenchima changes in neurofibromatosis type 1 - Ilić, Aleksandra; Raljević, Snežana; Adžić, Tatjana; Škodrić-Trifunović, Vesna; Stanimirović, Jelena (Vojnosanitetski pregled, 2017)
Introduction. Neurofibromatosis type 1 (NF1), also known as von Recklinghausen disease, is one of the most common single-gene disorders (mutation on chromosome 17q) and usually associated with cutaneous, musculoskeletal and neurological disorders in humans. NF1 is generally complicated with one or more neurobehavioral disorders or tumors located in the peripheral nervous system such as neurofibromas, peripheral nerve sheath tumor, pheochromocytoma, etc. In the available medical literature, the thoracic manifestations of NF1 have been rarely described in these patients. There are few reports about intrathoracic neurogenic tumors, kyphoscoliosis, pneumonitis and pulmonary fibrosis in patients with NF1. Case report. A 65-year-old female was admitted to the Intensive Care Unit at the Lung Clinic of Belgrade University Clinical Center of Serbia. The patient’s general condition was poor with shortness of breath and present cyanosis. At the same time, the skin changes similar to NF1 were noticed, which were additionally documented by her medical history and diagnosed as NF1. After the application of noninvasive mechanical ventilation and other emergency respiratory medicine measures, the patient soon felt better. The parenchymal changes were viewed by subsequent X-rays and CT scanning of the thorax. Conclusion. This is a case report presenting the NF1 associated with the abnormality of lung parenchyma established during diagnostic procedures at the Intensive Care Unit, Clinic of Pulmonology.
Keywords: neurofibromatoses; diagnosis; lung fibrosis; radiography; tomography; x-ray computed